Peran Media Infografis Dalam Meningkatkan Minat Belajar Siswa Bidang Studi Pai Di Sdn 02 Banjar Sari Labuhan Haji Lombok Timur - Nasri (Institute of Educational, Research, and Community Service, 2024)
This research aims to analyze the role of infographic media in increasing students' interest in learning in the subject of Islamic Religious Education on the material